Varför ska jag inte berätta? Litteraturarbete som språkintroduktion - Asklund, Jonas (Educare, 2018)
Discussions about books and ways of reading play an important role in the curriculum for the Swedish secondary school system. In an intervention study based on a series of book discussions of an easy reader novel, I investigated the cooperation between a group of Swedish language learners aged 16 to 19, their teacher in the introduction program for newcomers, and the school librarian. Based on my function as a teacher educator, and drawing on the current research in literature didactics, I planned and carried out six discussions where different reading strategies and methods were used. Using the concept of third space (Gutiérrez, 2008; Skerrett, 2010b) and interpersonal space(Cummins, 2000), I discuss the students’cognitive and emotional responses to the story we shared, and reflect upon the way these discussions have developed. Semi-structured interviews with five students, a teacher, and a school librarian constitute the data for this study. The analysis of the data indicates that the leader of the group discussion is instrumental in helping the participants shift between different perspectives, try out new roles, and transgress different boundaries, thereby offering the group different emotional, cognitive and linguistic challenges. Keywords: book talks, class room instruction strategies, interpersonal space, third space